A new strategy of efficiency enhancement for traction systems in electric vehicles. (1st November 2017) - Ding, Xiaofeng; Guo, Hong; Xiong, Rui; Chen, Feida; Zhang, Donghuai; Gerada, Chris
Highlights: A novel efficiency enhancement strategy for traction system was proposed. The proposed method supplies a fast search of the optimal variable (direct-axis current i d ). The maximum increment of the efficiency for the overall inverter-motor system was 2.7%. The saving of battery consumption is more than 9% due to the proposed strategy. The proposed method has been validated by the experimental test. Abstract: The inverter-motor drive system is the main traction force in electric vehicles (EVs). The overall efficiency of inverter-motor will directly determine the energy consumption of EVs. In this paper, aiming at improving the overall efficiency of inverter-motor, a novel methodology is proposed. Firstly, the iron loss, copper loss and stray loss of motor, as well as the devices' conduction loss and switching loss in inverter are modeled. Afterwards, based on previous loss model strategy and gold section search strategy, a novel hybrid efficiency-optimization control strategy is proposed. The proposed method combines each benefit in loss-model and gold section search, and can realize high efficiency operation of the inverter-motor system in large power range. Additionally, the proposed method manifests faster search speed and better accuracy compared to conventional methods. Experiment results validated the effectiveness of the proposed hybrid control strategy. Meanwhile, the impact of the efficiency improvement on the driving cycle is further investigated through Advanced Vehicle Simulator (ADVISOR) simulations.